The hundred dresses - Estes, Eleanor, 1906-1988.; Slobodkin, Louis, 1903-1975. (Orlando, Fla. : Harcourt, 2004)
In winning a medal she is no longer there to receive, a tight-lipped little Polish girl teaches her classmates a lesson. Includes a note from the author's daughter, Helena Estes.
6 to 10.
Newbery Honor Book, 1945
Keywords: Newbery Medal; Polish Americans -- Fiction; Friendship -- Fiction